PENGELOLAAN LAYANAN PERPUSTAKAAN SD NEGERI 34 PONTIANAK KOTA UNTUK MENINGKATKAN MINAT BACA BAGI SISWA - Septiana Septiana; Sisiliya Saman Madeten (Universitas Tanjungpura, 2021)
AbstractThe objectives of this research were to describe: 1). the library room service, 2).Reference service, 3). Circulation services, and 4). Efforts to increase students’interest in reading at SD Negeri 34 Pontianak Kota This research uses qualitativeresearch The sources of the research were the headmaster, the librarian, the teachers,as well as the students. The data gathering methods were observation, interview, anddocumentation. The validity of the data using Triangulation and Members Check Theresult of the research showed that the management of library services at SD Negeri 34Pontianak Kota to increase students' reading interest in terms of spatial services needsto be properly regulated again for the convenience of visitors, reference services helpreaders in finding the information needed, circulation services in the process ofborrowing and returning materials. literature is quite appropriate, and the effortsmade by librarians to increase students' reading interest by creating literacyprograms in each class.Keywords: Interest in reading, Library Services, Management